The Synergy of Village Developing Management through Corporate Social Responsibility Activities - Kolopaking, Lala Mulyowibowo; Septianto, Marzuqo; Ambarita, Ervan (Sodality: Jurnal Sosiologi Pedesaan, 2019)
Improvement the standard of living for villagers is increasingly open with the existence of UU No. 6 tahun 2014 concerning villages government. Various multistakeholders can strengthen village-based development mechanisms in synergy. The aim of this study is to analyze the synergy of the Corporate Social Responsibility management system with the management of a developing village by Indonesia Power PLTP Kamojang Branch Gunung Salak Ltd. This research is a policy research with a sequential mixed model design. Data were collected in the form of qualitative and quantitative data with methods of observation, interviews,and focused discussions. The results of the study show that Indonesia Power PLTP Kamojang Branch Gunung Salak Ltd and multistakeholders have succeeded in forming relations between different actors to improve village development. As for interacting with groups of people who are vulnerable to problems with their livelihood systems, corporate social responsibility mechanisms are improved based on the aspirations of the people who collaborate with multistakeholders from the planning stage to evaluating at the village to district level. Through this management mechanism assistance to the community can be done inclusive so that assistance can be recorded and measurable benefits.